PROTES SOSIAL DALAM NOVEL PULANG KARYA LEILA S. CHUDORI: PENDEKATAN SOSIOLOGI SASTRA - Peka Tariska; Widowati Widowati (Universitas Sarjanawiyata Tamansiswa, 2018)
The aims of the research are to describe these subjects. (1) Facts story from the novel Pulang; (a) plot, (b) characters and characterization, (3) The sttinngs which used by the author to show socialogical probtem in the novel. (4) CiviliansÂ pitcrures inÂ theÂ novelÂ â€œPulangâ€. (5) Social protest in the novel Â Pulang.Â This rescarchÂ isÂ oneÂ of the descriptiv ,qualitativeÂ rescarchâ€™sÂ kind . Data used in the from of sentecesÂ and pragrahs.Â TheseÂ dataÂ Â areÂ obtainedÂ Â fromÂ theÂ secondÂ colitionÂ Â ofÂ theÂ novel â€œPulangâ€Â byÂ LeilaÂ S . Chundori.Â The instruments ofÂ thisÂ researchÂ isÂ theÂ researsherÂ Â herselfÂ Â withÂ severalÂ theoriesÂ ofÂ intrinsic andÂ literatureâ€˜sÂ socialogical asÂ theÂ knifeÂ ofÂ analysis.Â TheÂ method and techniques of data collection used in this study are non-interactive and reading and note techniques.Â The method and techniques of data analysis in this research is descriptive method and descriptive analysis. The resultsÂ ofÂ thisÂ researchÂ Â areÂ Â asÂ Â follows. (1) Facts story from the novel â€œPulangâ€; (a) showingÂ thatÂ the authorÂ appliedÂ a flashbackÂ plot, (b) charactersÂ andÂ Â characterizationsÂ from the novelÂ â€œPulangâ€Â areÂ composed of one main character and four additional characterÂ with a simple gesture, Â (c)Â theÂ settingÂ inÂ thisÂ novelÂ areÂ tateingÂ placeÂ fromÂ someÂ citiesÂ ofÂ differentÂ countrry. byÂ usingÂ timeÂ intervalÂ onÂ 1998â€™sÂ Â social incident. (4)Â PicturesÂ ofÂ theÂ societyÂ capturedÂ inÂ this novelÂ Â areÂ fromÂ exiledÂ families,Â politicalÂ families,Â theirÂ Â limitnessÂ fromÂ someÂ accessÂ inÂ theÂ countryÂ andÂ Â their love to theirÂ nation. (5) The kind of social protest shown in the novel â€œPulangâ€ is a social-politics protest for the rulerÂ andÂ social- politicÂ protestÂ for society.